2022
DOI: 10.1590/1516-3180.2021.0356.27052021
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorders among pregnant women during the COVID-19 pandemic. A cross-sectional study

Abstract: BACKGROUND: Pregnancy is the most important event in women's lives and can lead to psychological lability. Several risk factors (such as disasters, events and pandemics) have been correlated with greater prevalence of mental disorders during pregnancy. OBJECTIVES: To research how pregnant women have been affected by the coronavirus disease-19 (COVID-19) pandemic process, in order to contribute to the limited literature. DESIGN AND SETTING: Cross-sectional survey study conducted at the Training and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 32 publications
0
14
2
Order By: Relevance
“…Some of the reported prevalence of anxiety are as follows: 39.1% in Nepal, 11 11.1% in India, 12 36.77% in China, 13 37.5% in Nigeria, 14 29.7% in Oman, 15 29.2% in Turkey, 16 and 52% in Netherlands. 17 The prevalence of anxiety reported in this study is lower than most of the other studies conducted in Nepal and other parts of the world. One of the main Free Full Text Articles are Available at www.jnma.com.np reasons for this inconsistency might be due to the different instruments used for data collection as these studies have mainly assessed generalised anxiety in pregnant women.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Some of the reported prevalence of anxiety are as follows: 39.1% in Nepal, 11 11.1% in India, 12 36.77% in China, 13 37.5% in Nigeria, 14 29.7% in Oman, 15 29.2% in Turkey, 16 and 52% in Netherlands. 17 The prevalence of anxiety reported in this study is lower than most of the other studies conducted in Nepal and other parts of the world. One of the main Free Full Text Articles are Available at www.jnma.com.np reasons for this inconsistency might be due to the different instruments used for data collection as these studies have mainly assessed generalised anxiety in pregnant women.…”
Section: Discussioncontrasting
confidence: 70%
“…Some of the reported prevalence of anxiety are as follows: 39.1% in Nepal, 11 11.1% in India, 12 36.77% in China, 13 37.5% in Nigeria, 14 29.7% in Oman, 15 29.2% in Turkey, 16 and 52% in Netherlands. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Our search identified 10 617 studies; 1231 full texts were reviewed, and of these, 203 studies were included (Figure 1; eTable 2 in Supplement 1). Cumulatively, outcomes were reported for 212 318 perinatal women (from conception to 12 months post birth) from 33 LMICs. The prevalence estimates of 6 anxiety and related disorders were reported: generalized anxiety disorder, social anxiety disorder, posttraumatic stress disorder, obsessive-compulsive disorder, panic disorder, and adjustment disorder.…”
Section: Resultsmentioning
confidence: 99%
“…46 53 Finally, in a Turkey-based study among pregnant women, mild sleepiness was found in 88.2% of participants (n=356), while severe sleepiness was reported in 11.8% of the same sample. 54 …”
Section: Resultsmentioning
confidence: 99%
“…46 53 Finally, in a Turkey-based study among pregnant women, mild sleepiness was found in 88.2% of participants (n=356), while severe sleepiness was reported in 11.8% of the same sample. 54 Children A total of 15 studies assessed sleep health among children. The sample size of studies ranged from 309 to 20 697 participants.…”
Section: Sleep Problemsmentioning
confidence: 99%